2019
DOI: 10.1111/mmi.14400
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate regulation of virulence and metabolic genes by the transcription factor HbhR in Mycobacterium marinum

Abstract: The heparin-binding hemagglutinin (HBHA) is a multifunctional protein involved in adherence ofMycobacterium tuberculosis to non-phagocytic cells and in the formation of intracytosolic lipid inclusions. We demonstrate that the expression of hbhA is regulated by a transcriptional repressor, named HbhR, in Mycobacterium marinum. The hbhR gene, located upstream of hbhA, was identified by screening a transposon insertion library and detailed analysis of a mutant overproducing HBHA. HbhR was found to repress both hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Our transcriptomic data indicated that MLDSR positively or negatively regulates several genes participating in diverse cellular functions, including lipid metabolism, redox metabolism, central metabolism, cellular stress, transport, or DNA processing, which probably contribute to the adaptation of the microorganism to fluctuating environmental conditions. A previous study demonstrated the role of the MLDSR ortholog, HbhR, as a master regulator linking the transcriptional regulation of virulence, metabolism, and antibiotic sensitivity genes in M. marinum [21]. However, we did not find a high correlation between the genes under the control of the respective regulatory proteins (MLDSR and HbhR) comparing transcriptomic data of R. jostii and M. marinum.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Our transcriptomic data indicated that MLDSR positively or negatively regulates several genes participating in diverse cellular functions, including lipid metabolism, redox metabolism, central metabolism, cellular stress, transport, or DNA processing, which probably contribute to the adaptation of the microorganism to fluctuating environmental conditions. A previous study demonstrated the role of the MLDSR ortholog, HbhR, as a master regulator linking the transcriptional regulation of virulence, metabolism, and antibiotic sensitivity genes in M. marinum [21]. However, we did not find a high correlation between the genes under the control of the respective regulatory proteins (MLDSR and HbhR) comparing transcriptomic data of R. jostii and M. marinum.…”
Section: Discussioncontrasting
confidence: 89%
“…Some of them are probably involved in TAG degradation and β‐oxidation of fatty acids (Table 2). A similar analysis was repeated by using the imperfect inverted repeat CTTGCAA(A/T)AGCAAG reported for Rv0474 [20] and HbhR [21], both homologs proteins of MLDSR in Mycobacterium tuberculosis and Mycobacterium marinum , respectively. Again, the best score corresponded to the binding site located upstream of the mldsr‐mlds cluster, and the occurrence of putative binding sequences was also present in upstream regions of some genes associated with lipid catabolism (Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations